Anemia and Mineral Bone Disorder in Patients with End Stage Renal Diseases on Maintenance Hemodialysis - Muhammad Mohsin Riaz, Aziz Ur Rahman, Syed Hyder Raza, Farheen Zehra, Nabeela Naeem, Gulmina Saeed Orakzai, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic kidney disease characterised by urinary disturbances or excretory kidney dysfunction, which is likely to result in functional nephron damage. Glomerulonephritis is an immune-mediated kidney inflammation that affects both the glomerulus and other parts of the kidney. The most common cause of end-stage renal disease is glomerulonephritis. The aim of this study to determine the anemia, mineral bone disorder and high low PTH level during hemodialysis. Study Design: This was cross-sectional study and conducted in the Ali Fatima Hospital Lahore, for six months March 2022 to August 2022. Materials and Methods: There were total 350 participants. The participants were selected by sampling technique were interviewed in the Khyber teaching hospital Peshawar. We analyzed dependent and independent variables. Data analysis statistically by SPSS 20 version. Results: There were total 350 participants which include71.4% males and 29% females in this research. The majority of the participants were in the age group (40-60) years or (n=350) 87% in the hemodialysis. The majority participants were mean age 49.2 ± 0.59 years. The participants were 69% financially depend upon family dialysis. The dialysis frequency of patients about 76% thrice per week and 24.2% were on twice per week. The hemoglobin level was <11 g/dL or mean 12.19±2.65 g/dL which show significantly reduced Hb level. The mean value of serum calcium, sodium, phosphorous and parathyroid levels in bone diseases were 165.40±6.91, 6.675±0.79, 6.89±2.64, and 255.63±233.71, which significantly changed in hemodialysis patients. Anti HCV is 80% positive in hemodialysis patients as compared to general population. Conclusion: The participants who suffered to maintained hemodialysis for > 3 months, majority have low level of Hb which cause anemia, low PTH which associate with the mineral bone diseases and also reduced serum Ca, P, k, Na and albumin level. Keywords: End stage renal disorder (ESRD), chronic kidney disorder (CKD).